Adam and its sonic world : authenticity and artistry - Fairuz Natasha Jumari (2019)
Adam is a film that has been pre-conceptualised to be auditorily tactile, emphasising on the intricacies of the everyday, and heightening audience sensitivities to the sonic space. It wishes to balance authenticity with artistry; encapsulating the authentic acoustic environment while not compromising on the possibilities of sound design.